Gelegenheitsarbeit einer Sklavin - Kluge, Alexander (Germany, 1973)
The film tells a story of a married mother of three at the centre of the protest movement. She finds her plans for social change are easier to realize outside family life.
The collections also contains: Lehrer im Wandel 1963, 11', Sam remembers Papa Kong 2006, 1'.
Options for the subtitles: English, French, Chinese, Russian, Spanish.
Keywords: Documentary films